Improving Writing Skills through the Writing Process Approach : from Theory to Practice (2023)
ABSTRACT : This action-research aimed at exploring how the implementation of the Writing Process Approach improve students writing skill particularly by writing a descriptive text. It was conducted in a public school in Rionegro, Antioquia with 35 sixth graders. Action strategies included three stages of the Writing Process Approach: Prewriting, Drafting and Revising. Data collection instruments included teacher’s journal, students’ artefacts, and a focus group. Findings referred to the positive impact and improvements in students’ writing skills in each stage in the Writing Process Approach in terms of composing, sentence formation and usage.